The Role and Challenges of Website-Based Management Information Systems in Organizations: A Literature Review - Andi Indriani Ibrahim; Sania Juniati Tabingke; Kristina Ntopu; Natalia Gitavia Barael; Nini Andriani; Ayu Putri Utami (Universitas Muhammadiyah Palu, 2026)
This study aims to examine the role, benefits, challenges, implementation, and development of technology in the application of website-based Management Information Systems (MIS) within organizations. The method used is a literature review of various relevant scientific sources published in the last five years. The results of the study indicate that web-based MIS significantly contributes to improving operational efficiency, information transparency, and the speed and accuracy of organizational decision-making. However, its implementation still faces various challenges, such as technological infrastructure readiness, human resource competence, implementation costs, resistance to change, and data security issues. Recent technological developments, such as the use of cloud servers and modern frameworks, have also promoted the flexibility and effectiveness of the system. This study provides conceptual and practical insights that organizations can use in designing effective and adaptive MIS implementation strategies in response to the dynamics of digital technology.